(untitled) (Third Sector Social Economic Review, 2023)
The Covid-19 pandemic and its restrictions have caused a turning point in the functioning of organizations. As a result, organizations have updated their policies to allow employees to work remotely. However, today, managers are concerned about the job performance of remote employees. Therefore, there are two divergent approaches which are bringing employees back to the office or allowing them to work remotely. This study aims to reveal the impact of remote working on employees’ job performance so that managers can make decisions. In the study, we obtained data from 174 remote workers in Somaliland by using a questionnaire. According to this study’s findings, remote working positively impacts employees’ task performance. In addition, the results showed that employees with high work experience performed better in remote work than those without work experience or with less work experience. This means that employees with more work experience can perform better. However, it is worth noting that other demographic characteristics such as gender, age, position, and education had no significant impact on the task performance of remote workers. Consequently, organizations should allow their employees to work remotely at least once or twice a week. This will increase employees’ motivation and enable them to fulfill their duties efficiently.